2019
DOI: 10.1038/s41366-018-0299-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of 15-week exercise training on dietary patterns among young adults

Abstract: BACKGROUND/OBJECTIVES: Little is currently known about how exercise may influence dietary patterns and/or food preferences. The present study aimed to examine the effect of a 15-week exercise training program on overall dietary patterns among young adults. SUBJECTS/METHODS: This study consisted of 2680 young adults drawn from the Training Intervention and Genetics of Exercise Response (TIGER) study. Subjects underwent 15 weeks of aerobic exercise training, and exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 56 publications
2
27
0
4
Order By: Relevance
“…Changes in exercise behaviour can also influence nutrition habits by application of self-regulatory psychological resources across behaviours; in particular exercise can facilitate improved fruit/vegetable consumption in young adulthood, a life-period critical to lay the foundation, based on the adoption of a health behaviour, for the prevention of metabolic diseases and for securing a healthy future with advancing age [23]. Joo et al [10] suggested that food choices differ depending on the type (intensity and duration) of the exercise performed. Despite this, to the authors' knowledge, scientific literature regarding the effects of different exercise modalities on dietary habits is still scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in exercise behaviour can also influence nutrition habits by application of self-regulatory psychological resources across behaviours; in particular exercise can facilitate improved fruit/vegetable consumption in young adulthood, a life-period critical to lay the foundation, based on the adoption of a health behaviour, for the prevention of metabolic diseases and for securing a healthy future with advancing age [23]. Joo et al [10] suggested that food choices differ depending on the type (intensity and duration) of the exercise performed. Despite this, to the authors' knowledge, scientific literature regarding the effects of different exercise modalities on dietary habits is still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the influence of exercise on dietary preferences is dependent on the type, method, frequency, duration and intensity of exercise performed; the sample sizes and characteristics may also affect the results [9]. Recently, Joo et al [10] reported that aerobic exercise of longer duration or higher intensity led to different dietary patterns, even though the trend was toward healthier diets in any case.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the preference for WD in male flies was decreased by exercise. This is supported by observations that exercise training in human subjects leads to healthier dietary preferences (79) and reduces overeating and reward for high-fat food (80).…”
Section: Accepted Articlementioning
confidence: 77%
“…In this line, Manz et al [43] reported a positive association of physical exercise and recommended daily physical activity with cereal intake among young boys, which suggest that nutritional adaptation as changes in food choices may occur as a response to physical activity [44]. According to the literature [45], a 15-week exercise training could help young adults pursuing healthier dietary preferences, as well as regulating their food intake in young adults. This could explain the between groups difference in DASH score, in which participants in the exercise group improved significantly more their diet quality according to DASH guidelines.…”
Section: Discussionmentioning
confidence: 99%